Performance of Graphene Zinc Powder Coating and Its Application in Radar Protection - YANG Jun - hua, CHEN Xu, WANG Wei, LIANG Yuan - jun, JIA Xue, ZHU Li - zhi (Cailiao Baohu, 2021)
In order to improve the adaptability of the radar to harsh marine environment, the properties of TP - GEP - 1 graphene zinc powder coating were studied, and it was found that the zinc content was obviously lower than that of zinc - rich coating, and the self corrosion potential of TP - GEP - 1 graphene zinc powder coating was also lower than that of Q345 steel. According to GB/T 30790.5, the coating system was composed of TP - GEP - 1, TH06 - 36 epoxy intermediate paint and TS96 - 61 fluorinated polyurethane topcoat. The anti - corrosive performance and temperature stress resistance of the coating system were tested based on GB/T 30790.6 and GJB 150, and the natural exposure in the atmosphere of Xisha was carried out. Results showed that the coating system had excellent anti - corrosive performance and temperature stress resistance, which could meet the durability requirements of the radar under harsh marine environment condition. Due to the excellent anti - corrosive performance, simple construction process and convenient quality control, the studied coating system has gradually been appied to domestic radar equipment in batches, which effectively improved the protection performance of radar under harsh marine environment.